The role of fillers to enhance the mechanical, thermal, and wear characteristics of polymer composite materials: A review - Yadav R.; Singh M.; Shekhawat D.; Lee S.-Y.; Park S.-J. (My University, 2025)
Humans have always relied heavily on materials in their daily lives. Humans have always used conventional materials to meet their needs, but new materials have had to be developed to meet the demands of modern society. By including novel elements, it is possible to change the characteristics of traditional materials. As a result, reinforcement (some additional material like fiber, nanoparticles, metal, etc.) is blended with conventional materials to increase their varied qualities. This review paper examines the impact of reinforcements on various polymer composite characterizations. Control variables for various wear analyses of polymer composites are also included. It was seen that fillers played a significant role in enhancing the mechanical, tribological, and erosive properties of polymer composites. © 2023